MENINGKATKAN KINERJA GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) INOVATIF MELALUI TEKNIK UMPAN BALIK PADA SMP NEGERI 1 PENDALIAN IV KOTO KABUPATEN ROKAN HULU - Eko Prayitno (STKIP ROKANIA, 2021)
This research is motivated by the lack of ability of teachers in designing innovative lesson plans, so as to create interesting learning. The purpose of this research is to increase the commitment of the teachers of SMP Negeri 1 Pendalian IV Koto to compose Innovative RPP in Job Training activities with Feedback techniques and to increase the ability of the teachers of SMP Negeri 1 Pendalian IV Koto to compose Innovative RPP in Job Training activities. with the Feedback technique. The method in this research is Classroom Action Research (CAR). This research method is qualitative and quantitative methods. The results showed an increase in the value of the commitment of teachers to make Innovative RPP from cycle I to cycle III of 0.93 (on a scale of 1-5) from 3.41 to 4.33. The number of teachers who achieved a score of more than 4.00 was 16 people (94%). The percentage increase was 68%, from 26% to 94%. So the performance indicators for increasing the commitment of teachers by 85% of the number of teachers have been achieved in cycle III with the achievement of 94%